ELECTROPHYSIOLOGICAL PROPERTIES OF MORPHOLOGICALLY-IDENTIFIED MEDIAL VESTIBULAR NUCLEUS NEURONS PROJECTING TO THE ABDUCENS NUCLEUS IN THE CHICK EMBRYO - Gottesman-Davis, Adria (2010)
Neurons in the medial vestibular nucleus (MVN) show a wide range of axonal projection pathways, intrinsic firing properties, and responses to head movements. To determine whether MVN neurons participating in the vestibulocular reflexes (VOR) have distinctive electrophysiological properties related to their output pathways, a new preparation was devised using transverse brain slices containing the chicken MVN and abducens nucleus. Biocytin Alexa Fluor was injected extracellularly into the abducens nucleus so that MVN neurons whose axons projected to the ipsilateral (MVN/ABi) and contralateral (MVN/ABc) abducens nuclei were labeled selectively. Whole-cell, patch-clamp recordings were performed to study the active and passive membrane properties, sodium conductances, and spontaneous synaptic events in morphologically-identified MVN/AB neurons and compare them to MVN neurons whose axons could not be traced (MVN/n). Located primarily in the rostral half of the ventrolateral part of the MVN, MVN/AB neurons mainly have stellate cell bodies with diameters of 20-25 μm. Compared to MVNn neurons, MVN/ABi and MVN/ABc neurons had lower input resistances. Compared to all other MVN neuron groups studied, MVN/ABc neurons showed unique firing properties, including type A-like waveform, silence at resting membrane potential, and failure to fire repetitively on depolarization. It is interesting that the frequency of spontaneous excitatory and inhibitory synaptic events was similar for all the MVN neurons studied. However, the ratio for miniature to spontaneous inhibitory events was significantly lower for MVN/ABi neurons compared to MVN/n neurons, suggesting that MVN/ABi neurons retained a larger number and/or more active inhibitory presynaptic neurons within the brain slices. Also, MVN/ABi neurons had mEPSCs with slower decay time and half width compared to MVN/n neurons. Altogether, these findings underscore the diversity of electrophysiological properties of MVN neuron classes distinguished by axonal projection pathways. This represents the first study of MVN/AB neurons in brain slice preparations and supports the concept that the in vitro brain slice preparation provides an advantageous model to investigate the cellular and molecular events in vestibular signal processing.